2014
DOI: 10.1155/2014/371403
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Synchronization Digital Control for Double Hydraulic Cylinders

Abstract: By researching the synchronization motion of double hydraulic cylinders controlled by high-speed on-off valve, the paper aims to solve the shortage of current hydraulic synchronization system with low synchronization precision. The flow characteristic of high-speed on-off valve with pulse width-frequency modulation is researched compared with pulse width modulation. The mathematical equations of the double hydraulic cylinders are formulated with bulk-cavity-node method in MATLAB/Simulink. The collaborative syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In the case of manually adjustable hydraulic resistance, this boils down to the use of a throttle valve and in the case of automatically adjustable hydraulic resistance, the use of a flow regulator. In both cases, the idea of solving the problem of motion synchronization boils down to creating additional pressure drops in the power supply branches of individual drives so that the pressure in the pump discharge line, determined from the equilibrium pressure equations arranged for the power branches of individual drives, is the same [10][11][12].…”
Section: Synchronous Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of manually adjustable hydraulic resistance, this boils down to the use of a throttle valve and in the case of automatically adjustable hydraulic resistance, the use of a flow regulator. In both cases, the idea of solving the problem of motion synchronization boils down to creating additional pressure drops in the power supply branches of individual drives so that the pressure in the pump discharge line, determined from the equilibrium pressure equations arranged for the power branches of individual drives, is the same [10][11][12].…”
Section: Synchronous Movementmentioning
confidence: 99%
“…The position synchronization error looks for the difference between the position errors of many axes and is based on the synchronization function (12).…”
Section: Levellingmentioning
confidence: 99%
“…The simplest approach is to design a flow divider circuit that will maintain the same cylinder speed by maintaining the same flow rate for the cylinders. The efficiency of the synchronization depends on the efficiency of the flow distributor, as well as the compressibility of the working fluid and the consistency of the hydraulic components (Liu et al, 2014). Another solution is the mechanical connection of hydraulic cylinders by means of cabling or other switching construction.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant research on the vibration characteristics of high-frequency vibration systems used in cleaning or other cases. Liu et al 10 researched the synchronization motion of double hydraulic cylinders controlled by high-speed on-off valve and found that the collaborative synchronization control is effective to eliminate displacement error between the double cylinders which results from the different load environment and other disturbances. Wan et al 11 proposed a dynamic self-adaptive mixed control method.…”
Section: Introductionmentioning
confidence: 99%